Efficacy and safety of clarithromycin for patients with sepsis or septic shock: a systematic review and meta-analysis - Pengyue Zhao; Renqi Yao; Jiaqi Yang; Wei Wen; Yongming Yao; Xiaohui Du (Emergency and Critical Care Medicine)
Abstract. Background. Clarithromycin exerts an immunomodulatory role in several human diseases. However, whether this effect improves the prognosis in patients with sepsis remains controversial, and higher levels of clinical evidence are urgently needed. To the best of our knowledge, no meta-analysis to date has reported the clinical efficacy and safety of clarithromycin in sepsis. Methods. A comprehensive literature search of PubMed, EMBASE, and the Cochrane Library was conducted up to December 31, 2022. Only randomized controlled trials comparing the clinical efficacy and safety of clarithromycin with controls among patients with sepsis or septic shock were included. Data were pooled by applying a fixed-effects model and a relative risk (RR) estimate with 95% confidence intervals (CIs) using Review Manager (version 5.3; Cochrane Collaboration, Copenhagen, Denmark). Results. Three randomized controlled trials involving a total of 910 patients were included. The pooled results confirmed that clarithromycin had no beneficial effect on progression to multiple organ dysfunction syndrome (RR: 1.51; 95% CI: 1.02–2.25; P = 0.04; I2 = 0%), 28-day mortality (RR: 1.09; 95% CI: 0.87–1.36; P = 0.46; I2 = 0%), and 90-day mortality (RR: 0.86; 95% CI: 0.71–1.03; P = 0.10; I2 = 81%) in patients with sepsis or septic shock. Moreover, there was no difference in other serious adverse events between patients who received clarithromycin and those in the control group (RR: 1.02; 95% CI: 0.87–1.19; P = 0.83; I2 = 18%). Conclusion. Our meta-analysis did not reveal an improvement to short-term outcomes in patients with sepsis treated with clarithromycin. However, administration of clarithromycin did not increase the risk of adverse events.